The unusual suspects - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2005)
Although filled with anger over her parents' disappearance, eleven-year-old Sabrina Grimm-- along with her grandmother, sister, and several fairy-tale characters-- tries to discover who has killed her teacher.